Multidrug Resistant Enteric Bacterial Pathogens in a Psychiatric Hospital in Ghana: Implications for Control of Nosocomial Infections - Kwabena O. Duedu; George Offei; Francis S. Codjoe; Eric S. Donkor (International Journal of Microbiology)
Enteric bacteria are commonly implicated in hospital-acquired or nosocomial infections. In Ghana, these infections constitute an important public health problem but little is known about their contribution to antibiotic resistance. The aim of the study was to determine the extent and pattern of antibiotic resistance of enteric bacteria isolated from patients and environmental sources at the Accra Psychiatric Hospital. A total of 265 samples were collected from the study site including 142 stool and 82 urine samples from patients, 7 swab samples of door handle, and 3 samples of drinking water. Enteric bacteria were isolated using standard microbiological methods. Antibiograms of the isolates were determined using the disc diffusion method. Overall, 232 enteric bacteria were isolated. Escherichia coli was the most common (38.3%), followed by Proteus (19.8%), Klebsiella (17.7%), Citrobacter (14.7%), Morganella (8.2%), and Pseudomonas (1.3%). All isolates were resistant to ampicillin but sensitive to cefotaxime. The resistance ranged from 15.5% to 84.5%. Multidrug resistance was most prevalent (100%) among isolates of Proteus and Morganella and least prevalent among isolates of Pseudomonas (33.3%). Multidrug resistance among enteric bacteria at the study hospital is high and hence there is a need for screening before therapy to ensure prudent use of antibiotics.